Lymphocutaneous sporotrichosis: clinical suspicion when lesion is refractory to antibacterial treatment - Che' Man, Mohamad; Wan Mahmud, Wan Fatimah Suriyani; Ismail, Rasimah (The Ministry of Health and Universiti Brunei Darussalam, 2022)
Sporotrichosis is a fungal infection caused by Sporothrix schenckii. It occurs worldwide especially in tropical and subtropical areas. It manifests as lymphocutaneous skin, fixed cutaneous or disseminated lesion following exposure to contaminated source like animals, plants, or abiotic components. We report a case of a 75-year-old lady with right foot ulcerative nodule which was refractory to repeated antibacterial treatment, and cultures were all negative including mycobacterium and fungus. Skin punch biopsy was also negative for granuloma or malignancy. Based on the history, physical examination and investigation findings, a clinical suspicion of lymphocutaneous sporotrichosis was made. The patient was started on an empirical course of itraconazole 200mg od. The lesions responded well with 12 weeks of treatment. As clinicians we are occasionally faced with cases where investigations may not yield results that are helpful towards making a diagnosis and in such situations, we may need to start empirical treatment based on our best judgement.